2016
DOI: 10.1109/tnnls.2015.2460991
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Implementation of the Backpropagation Algorithm in FPGAs and Microcontrollers

Abstract: The well-known backpropagation learning algorithm is implemented in a field-programmable gate array (FPGA) board and a microcontroller, focusing in obtaining efficient implementations in terms of a resource usage and computational speed. The algorithm was implemented in both cases using a training/validation/testing scheme in order to avoid overfitting problems. For the case of the FPGA implementation, a new neuron representation that reduces drastically the resource usage was introduced by combining the input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 34 publications
1
45
0
3
Order By: Relevance
“…It can be appreciated from the error curves that for the FPGA implementation case some larger oscillations appear, and this is due to rounding effects because of the size of the fixed point representation used. In terms of the level of prediction accuracy obtained these oscillations do not degrade it, and on the contrary in some cases even leads to larger values, as it has been observed previously in FPGA implementations [31,33], and in several works where it was concluded that certain level of noise might be beneficial for improving learning times, fault tolerance and prediction accuracy [1,15,26]. Table 3 shows the generalization ability obtained for several architectures with different numbers of hidden layers for the FPGA and MC implementations.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…It can be appreciated from the error curves that for the FPGA implementation case some larger oscillations appear, and this is due to rounding effects because of the size of the fixed point representation used. In terms of the level of prediction accuracy obtained these oscillations do not degrade it, and on the contrary in some cases even leads to larger values, as it has been observed previously in FPGA implementations [31,33], and in several works where it was concluded that certain level of noise might be beneficial for improving learning times, fault tolerance and prediction accuracy [1,15,26]. Table 3 shows the generalization ability obtained for several architectures with different numbers of hidden layers for the FPGA and MC implementations.…”
Section: Resultssupporting
confidence: 76%
“…The first column indicates the number of hidden layer present in the architecture, the second column shows the generalization obtained using the MC implementation (mean and standard deviation computed over 100 independent runs using C code), while third and fourth columns shows the results for two different FPGA implementations: the layer multiplexing scheme proposed in this work and the fixed layer scheme utilized in Ref. [31] (only available for architectures with one and two hidden layers). The number of neurons in each of the hidden layers was fixed to five and the number of epochs set to 1000.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The key operations for the training and inference processes of DNNs are the vector‐matrix product, nonlinear function execution, and weights matrix update, while SNNs require spiking neurons and synaptic devices. To accelerate DNNs, various computing systems have been designed as DL accelerator (DLA), for instance, the FPGA based platforms, ASIC based TPU, DianNao, etc . These DLAs use a novel computing architecture to expedite training or the inference process of DNNs.…”
Section: Introductionmentioning
confidence: 99%